Targeting Membrane Lipid a Potential Cancer Cure? - Tan, Loh Teng-Hern; Chan, Kok-Gan; Pusparajah, Priyia; Lee, Wai-Leng; Chuah, Lay-Hong; Khan, Tahir Mehmood; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2017)
Cancer mortality and morbidity is projected to increase significantly over the next few decades. Current chemotherapeutic strategies have significant limitations, and there is great interest in seeking novel therapies which are capable of specifically targeting cancer cells. Given that fundamental differences exist between the cellular membranes of healthy cells and tumor cells, novel therapies based on targeting membrane lipids in cancer cells is a promising approach that deserves attention in the field of anticancer drug development. Phosphatidylethanolamine (PE), a lipid membrane component which exists only in the inner leaflet of cell membrane under normal circumstances, has increased surface representation on the outer membrane of tumor cells with disrupted membrane asymmetry. PE thus represents a potential chemotherapeutic target as the higher exposure of PE on the membrane surface of cancer cells. This feature as well as a high degree of expression of PE on endothelial cells in tumor vasculature, makes PE an attractive molecular target for future cancer interventions. There have already been several small molecules and membrane-active peptides identified which bind specifically to the PE molecules on the cancer cell membrane, subsequently inducing membrane disruption leading to cell lysis. This approach opens up a new front in the battle against cancer, and is of particular interest as it may be a strategy that may be prove effective against tumors that respond poorly to current chemotherapeutic agents. We aim to highlight the evidence suggesting that PE is a strong candidate to be explored as a potential molecular target for membrane targeted novel anticancer therapy.